Human talent development processes in a specialty clinic in Pasto, Colombia - Matabajoy-Montilla, Jeraldine Milena; Matabanchoy-Tulcán, Sonia Maritza; Obando-Guerrero, Lina Maria (Universidad y Salud, 2018)
Introduction: Workers in the organization play a fundamental role in meeting the corporate objectives. In this sense, it is important to identify the processes of human talent development in the health sector since they contribute to human and organizational development. Objective: The processes of human talent development training, quality of work life, occupational health, organizational climate and performance evaluation were characterized in a specialty clinic in the city of Pasto, Colombia. Materials and methods: The study was addressed from the quantitative paradigm of descriptive type with a sample of 211 collaborators. The scale called "perception of human talent development processes" was built, whose Alfa de Cronbach was 0.97. Results: The results were systematized in the statistical program IBM SPSS statistics. Statistically significant differences were found in the training category (in the categories of needs detection, plan and programmes, training evaluation and follow-up), quality of working life (in the sub-categories: meaning of work and labor commitment) and performance evaluation (in the subcategories: methods and results). Conclusions: The need to continue strengthening the processes of training, quality of work life and evaluation of performance is recognized.